Steric and Electrostatic Effects on the Diffusion of CH4/CH3OH in Copper-Exchanged Zeolites: Insights from Enhanced Sampling Molecular Dynamics and Free Energy Calculations - Freitas, Luis Paulo M. [UNESP]; Espírito Santo, Anderson A. [UNESP]; Lourenço, Tuanan C.; Da Silva, Juarez L. F.; Feliciano, Gustavo Troiano [UNESP] (American Chemical Society (ACS), 2021)
Copper-exchanged zeolites have demonstrated high selectivity in methane-to-methanol conversion carried out on copper-oxo centers. Nevertheless, the reaction can only occur if the methane molecules reach the active site while the methanol molecules must leave the material without high energetic cost for the migration. In this context, we have used force field-based molecular dynamics simulations with the potential of mean force method to estimate the energy barrier in cage to cage diffusion of methane and methanol molecules in the chabazite framework type zeolite. The results show considerably higher energy barrier for methanol diffusion. The steric effect of the active site and the electrostatic environment favors the CH3OH diffusion toward nonactive cages where it tends to accumulate due to the strong interactions with the zeolite. The same behavior is observed in the water molecules distribution, which emphasizes the control of the electrostatic potential over the polar molecules migration. For high concentration of polar molecules, the electrostatic effect is shielded and the driving force is reduced for CH3OH diffusion. The results show that if the electrostatic environment can be controlled, the product migration may be facilitated, which can improve the catalytic process.